Bed Rest Worsens Impairments in Fat and Glucose Metabolism in Older, Overweight Adults - Coker, Robert H. (Oxford University Press, 2014)
BACKGROUND. The effects of bed rest on the dysregulation of fatty acid and glucose metabolism have not been addressed in the older population. OBJECTIVE. We examined the effect of 10 days of bed rest on fatty acid kinetics and hepatic and peripheral insulin resistance in aging. METHODS. We utilized an octreotide, basal glucagon replacement, multistage insulin infusion, and the concomitant infusion of [6,6 (2)H(2)]glucose to derive insulin-mediated suppression of glucose production and insulin-stimulated glucose disposal in nine older, overweight individuals (body mass index 28.1 ± 1.7 kg m(−2); 39.9% ± 1.9% fat). During the multistage insulin infusion, we also infused [1-(13)C]palmitate to examine free fatty acid rate of appearance (R (a)). RESULTS. Body weight, % body fat, and energy metabolism did not change with bed rest. There was a significant decrease (−2291 ± 316cm(3)) in visceral fat, and no change in abdominal subcutaneous fat with bed rest. Insulin-mediated suppression of glucose production was modest prior to bed rest and was further reduced (>15% ± 2%) by bed rest. There was also a minor decrease in the insulin-mediated suppression of free fatty acid R (a) after bed rest and, as a consequence, a small variation in plasma free fatty acid from pre- to post-bed rest in the first stage of the multistage insulin infusion. There was also a significant bed rest–induced decline (>2.0 ± 0.6 mg kg FFM(−1) min(−) (1)) in insulin-stimulated glucose disposal. CONCLUSIONS. Preexisting impairments in insulin sensitivity are worsened by bed rest and seem linked to alterations in the regulation of free fatty acid in older, overweight individuals.